1983
DOI: 10.1002/1097-0142(19831215)52:12<2349::aid-cncr2820521231>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system metastasis from breast carcinoma autopsy study

Abstract: Central nervous system (CNS) metastasis was noted in 309 patients of 1044 autopsy cases of breast carcinoma. The brain was involved in 193 cases, and cranial dura in 167 cases. In 82 cases, the cranial dura was the sole site of CNS involvement. Metastasis to the leptomeninges was found in 59 cases, and to the spinal cord and dura in 32 cases. Metastases to the infratentorial portion of the brain was almost as frequent as to the cerebrum. Forty‐two percent of the brain metastasis were single lesions, which is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
297
3
3

Year Published

1986
1986
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 551 publications
(319 citation statements)
references
References 10 publications
(2 reference statements)
16
297
3
3
Order By: Relevance
“…These percents are supported by other autopsy studies, which found 42% of brain metastases of breast cancer patients were single lesions [145,147]. One retrospective study found only 15.3% of patients had single lesions [155].…”
Section: Distribution Of Cns Metastasissupporting
confidence: 64%
See 2 more Smart Citations
“…These percents are supported by other autopsy studies, which found 42% of brain metastases of breast cancer patients were single lesions [145,147]. One retrospective study found only 15.3% of patients had single lesions [155].…”
Section: Distribution Of Cns Metastasissupporting
confidence: 64%
“…Within the parenchyma, the brain tissue, brain metastasis is most common in the cerebral hemispheres [4,145]. Up to 85% of brain metastases occur in these hemispheres, whereas only 10% to 25% occurs in the cerebellum and 1% to 3% in the brain stem [146,147].…”
Section: Distribution Of Cns Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Brain is among the most common sites of relapse in breast cancer, with the clinical and autopsy occurrence of 14-20% and 18-30%, respectively [1,2]. Relapse in the brain is related to high morbidity and mortality, with relatively few effective therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…6 The most common malignant tumors in the brain are metastases, with up to 50% of cancer patients eventually developing brain metastases. 9 Melanoma, while not the most common cancer, has the greatest likelihood to metastasize to the brain with B50% clinically diagnosed and up to 80% at autopsy. 10 In lung cancer, brain metastases are common with about 10% of patients presenting with small-cell lung cancer having brain metastases and rising to B40% at autopsy.…”
Section: Introductionmentioning
confidence: 99%